ЕКСПЕРИМЕНТАЛЬНІ ДОСЛІДЖЕННЯ СИСТЕМИ МЕДИЧНОГО ДІАГНОСТУВАННЯ ПАЦІЄНТІВ ЗА АНАЛІЗОМ КРОВІ НА ОСНОВІ НЕЙРОННОЇ МЕРЕЖІ КОХОНЕНА - Колесницький, О. К.; Журавська, Ю. О. (Vinnytsia National Technical University, 2014)
This paper describes the results of experimental researches of  program system of the medical diagnostics of patients based on blood test. The proposed system uses a Kohonen neural network, in which the cluster centers are determined in advance in accordance with normal and deviations from the normal values of the parameters of a general blood test.